The measurement of military unit capabilities to eguip the guard on convoying, extradition and the convict security - Skripnyuk S. І. (Honor and Law, 2019)
The waus to measure military unit capabilities to egnip the guard on convoying, extradition and the convict security on the basis of convoying units strength are considered. The approaches to calculate the index that characterizes the capabilities are offered.